Inter-oceanic movement of an adult female humpback whale between Pacific and Atlantic breeding grounds off South America - Stevick, Peter T.; Allen, Judith M.; Engel, Marcia H.; Felix, Fernando; Haase, Ben; Neves, Mariana C. (J. Cetacean Res. Manage., 2023)
We report the first documented movement of an individual humpback whale between the eastern South Pacific stock off Ecuador and the western South Atlantic stock off Brazil. This constitutes the first record of a humpback whale in both the Atlantic and Pacific breeding grounds off South America, and one of a small number of inter-oceanic movements documented to date. It is possible that, even at quite low levels, this movement of individuals between breeding grounds contributes to the current high level of mtDNA diversity in these once-depleted Southern Hemisphere populations. When first sighted, the whale was accompanied by a young calf, and is therefore identified as an adult female. This movement to a different and distant breeding ground is the first reported by a reproductively mature female, and shows that extreme long-distance travellers among humpback whales are not restricted to young males.